Knowledge sharing and innovation capability / Siti Sarah Rosmi and Sharifah Khairol Musairah - Rosmi, Siti Sarah; Khairol Musairah, Sharifah (Universiti Teknologi MARA, Perlis, 2017)
The study was done to investigate the effect of individual predictors (enjoyment in helping others and knowledge self-efficacy), organizational predictors (top management support and organizational rewards) and technology predictors (information and communication technology use) on knowledge sharing processes and if the predictors lead to innovation capability. The result of the study indicated that one individual factor (knowledge self-efficacy) and two organizational factors (top management support and organizational rewards) significantly affect knowledge sharing. Future research can investigate how individual traits (such as age, education level, and work experience) and organizational characteristics (such as organizational size and type) may either mediate or moderate the relationships between knowledge enablers and processes. From the managerial viewpoint, the associations among knowledge sharing enablers, processes, and organization innovation capability may shed a light on how organizations can motivate knowledge sharing culture among their employees to maintain their performance. The results of this research provide a conceptual foundation towards the body of knowledge in the field of knowledge sharing and can also be utilized to investigate the relationships among knowledge sharing predictors, enablers, processes, and innovation capability. In terms of practical perspective, this research provided several predictors that are necessary towards successful knowledge sharing, and discussed the implications of the predictors in order to develop organizational strategies that encourage and improve knowledge sharing among employees.